Deciphering perivascular macrophages and microglia in the retinal ganglion cell layers - Jeon, Jehwi; Park, Yong Soo; Kim, Sang-Hoon; Kong, Eunji; Kim, Jay; Yang, Jee Myung; Lee, Joo Yong; Kim, You-Me; Kim, In-Beom; Kim, Pilhan (Frontiers in Cell and Developmental Biology, 2024)
The classically defined two retinal microglia layers are distributed in inner and outer plexiform layers. Although there are some reports that retinal microglia are also superficially located around the ganglion cell layer (GCL) in contact with the vitreous, there has been a lack of detailed descriptions fully understood yet. We visualized the microglial layers by using CX3CR1-GFP transgenic mice with both healthy and disease conditions. Although microglia in the superficial layer are located near the outer plexiform layer and not easy to distinguish between the two layers in normal conditions, each microglial layer respectively gets closer to near retinal capillary plexus, including the superficial, intermediate, and deep capillary plexus, making inter-glial distances more visible and larger in the disease models. The GCL microglia has two subsets; peripheral (pph) microglia located on the retinal parenchyma and BAM (CNS Border Associated Macrophage) which have a special stretched phenotype only located on the surface of large retinal veins. First, in the pph microglia subset, but not in BAM, Galectin-3 and LYVE1 are focally expressed. However, LYVE1 is specifically expressed in the amoeboid or transition forms, except in the typical dendritic morphology in the pph microglia. Second, BAM is tightly attached to the surface of the retinal veins and has similar morphology patterns in both the healthy and disease conditions. CD86+ BAM has a longer process that vertically passes the proximal retinal veins. Our data helps decipher the basic anatomy and pathophysiology of the retinal microglia in the GCL.